Application of electromagnetic navigation guidance technology in enteral nutrition support for a case of severe acute pancreatitis with duodenal fistula: a case report - Zhou, Jun; Huang, Yalan; Rong, Yuping; Wang, Xiusi; Yang, Qiang (Frontiers in Medicine, 2025)
A female patient with severe acute pancreatitis (SAP) complicated by infected pancreatic necrosis (IPN) developed a descending duodenal fistula during the sixth week of disease progression. Enteral nutrition (EN) delivery was hindered by occlusion of the nasojejunal tube in another hospital. We successfully placed a nasojejunal tube under electromagnetic navigation and initiated enteral nutrition support. This report highlights the application of this nutritional support technology in patients with high-output complex intestinal fistula.